The arteriel blood supply of brain in angora goats - I. Hakkı Nur (Eurasian Journal of Veterinary Sciences)
This study was made to investigate the arterial blood supply of brain in Angora goats. In this study, ten heads of Angora goats were used. In the investigation of the materials, latex was tnjected through the carotid comman artery. The brain is supplied with the internal carotid artery arising from the rete mirabile epidurale rastrale that is formed by maxillar artery, not with branches of the vertebral artery, condylar artery and meningeal medial artery. Giving the cerebral medial artery, the internal carotid artery continues as the cerebral rastral artery. The right and left cerebral rostral arteries are connected by means of the communicans rastral arteries. The corporis cal!osi artery arises from the connecting angle. The marginal artery runs in very strong dura mater sheath and it gives the ethmoidal internal artery. The communicans caudal artery is the caudal extention of the carotid internal artery. The basi/ar artery is formed connecting the right and left communicans arteries. The basilar artery gives the medullar and paramedian branches. The basilar artery continues as the spinal ventral artery on the cauda/ part of the medulla oblongata. The labyrinthine artery arises from the cerebellar caudal artery.